2020
DOI: 10.1101/2020.10.10.20207449
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recovery of monocyte exhaustion is associated with resolution of lung injury in COVID-19 convalescence

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection resulting in the clinical syndrome COVID-19 is associated with an exaggerated immune response and monocyte infiltrates in the lungs and other peripheral tissues. It is now increasingly recognised that chronic morbidity persists in some patients. We recently demonstrated profound alterations of monocytes in hospitalised COVID-19 patients. It is currently unclear whether these abnormalities resolve or progress following patient discharge. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…In our post-COVID19 patients, however, the monocyte and myeloid pools in both the airways and peripheral blood appear to have returned to relatively normal numbers and their frequency does not correlate with indicators of ongoing epithelial damage. Likewise, their activation status, as determined by HLA-DR and CD86 expression, is not substantially different between individuals in line with other reports on circulating monocytes from earlier stages of convalescence (Scott et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our post-COVID19 patients, however, the monocyte and myeloid pools in both the airways and peripheral blood appear to have returned to relatively normal numbers and their frequency does not correlate with indicators of ongoing epithelial damage. Likewise, their activation status, as determined by HLA-DR and CD86 expression, is not substantially different between individuals in line with other reports on circulating monocytes from earlier stages of convalescence (Scott et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…The copyright holder for this preprint this version posted August 10, 2021. ; https://doi.org/10.1101/2021.08.10.21261834 doi: medRxiv preprint Immune-proteome landscape post-COVID19 substantially different between individuals in line with other reports on circulating monocytes from earlier stages of convalescence (Scott et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Emerging transcriptomic evidence shows that changes in blood myeloid cells elicited during acute infection can normalize within 14 days of becoming SARS2-CoV-2 negative (56). However, some changes can persist for at least 12 weeks, including high levels of surface molecules that regulate monocyte migration into tissue e.g., CXCR6 and VLA-4 (57). We found that in contrast for example to IL-6, plasma SPP1 and S100A12 remained significantly higher than normal for at least 10 weeks after infection clearance in the post-COVID-19 convalescent phase.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 infection results in formation of long-lasting systemic immunological memory, with virus-specific antibodies and T cell responses still detectable in the majority of those infected at least 8 months post infection and higher titers seen in previously hospitalized individuals (Dan et al, 2021). Circulating lymphocyte counts and the function and frequency of monocytes are also reduced during acute disease, but they appear to return to normal shortly after resolution of acute disease (Mann et al, 2020;Scott et al, 2020).…”
Section: Introductionmentioning
confidence: 99%